Teaching Writing through Guiding Questions Technique to Improve Students’ Writing Skill - Firdani Firdani; Siti Sarah Fitriani (Research in English and Education Journal, 2017)
Writing is not an easy skill to acquire for EFL students, especially without intense help from teachers. This research was aimed to examine whether students’ ability in all aspects of writing can be improved by using Guiding Questions technique or not. To do so, the writer used factual report text. In addition, the writer employed quantitative research with one group pretest and posttest. Through random sampling, the writer took 21 out of 115 second grade students of MAN Darussalam Aceh Besar to be involved in this research. The result reveal that the mean score of posttest is higher than the mean score of pretest (54.8771.02) and the value of t-score is higher than the value of t-table (14.  2.086). Therefore, it can be concluded that the use of Guiding Questions technique in teaching writing improves the students’writing performance. Moreover, out of all the writing aspects, content and organization are two of the highest improved aspects. Hence, Guiding Questions technique is recommended as a good technique in teaching writing.